Molecular iodine-promoted oxidative cyclization for the synthesis of 1,3,4-thiadiazole-fused- [1,2,4]-thiadiazole incorporating 1,4-benzodioxine moiety as potent inhibitors of α-amylase and α-glucosidase: In vitro and in silico study - Hussain, Rafaqat; Shah, Mazloom; Iqbal, Shahid; Rehman, Wajid; Khan, Shoaib; Rasheed, Liaqat; Naz, Haseena; Al-ghulikah, Hanan A.; Elkaeed, Eslam B.; Pashameah, Rami Adel; Alzahrani, Eman; Farouk, Abd-ElAziem (Frontiers in Chemistry, 2022)
Twenty-five analogs were synthesized based on 1,3,4-thiadiazole-fused-[1,2,4]-thiadiazole incorporating 1,4-benzodioxine moiety (1–25) and then tested for the antidiabetic profile. The entire afforded derivatives showed varied inhibition profiles ranging between 0.70 ± 0.01 and 30.80 ± 0.80 μM (against α-amylase) in comparison to standard acarbose (12.80 ± 0.10 μM). Similarly, synthetics analogs also displayed a varied range of α-glucosidase activity ranging from 0.80 ± 0.01 μM to IC50 = 29.70 ± 0.40 μM (against α-glucosidase) as compared to standard acarbose (IC50 = 12.90 ± 0.10 μM). Among synthesized analogs, compound 22 showed excellent potency due to the presence of di-hydroxy substitutions at the 2,3-position of the aryl ring. For all analogs, the structure–activity relationship was carried out based on the pattern of substitutions around the aryl ring, and further, the potent analogs were subjected to a molecular docking study to analyze how active residues of targeted enzymes interact with active parts of newly prepared analogs. The result obtained shows that these compounds furnish several key interactions with enzyme active sites and, hence, enhanced their enzymatic activities.